Strategi Dosen dalam Pengondisian Perilaku Membaca Mahasiswa di Era Digital: Studi Kasus di Kalimantan Barat dan Sulawesi Selatan - Andina, Elga (Jurnal Aspirasi, 2017)
Reading is an activity that helps develop college student’s thinking ability, as well as support academic performance and achievement. This study wanted to know how the role of lecturers in shaping student’s reading behavior in the digital era. By interviewing 26 lecturers, 38 students, 2 university library heads and an officer of provincial education authorities, this study found that students' reading behavior did not grow due to lack of guidance in the previous education level. Interaction with information technology and telecommunications in the digital era increasingly keeps students away from the expected reading behavior. Intervention of the lecturer becomes important in conditioning the reading behavior, that is with the assignment of notes and the assignment of reading. In addition, universities need to prepare facilities and infrastructures that support the growth of student’s reading behavior.Membaca adalah kegiatan yang membantu mengembangkan pemikiran mahasiswa sehingga mendukung performa dan pencapaian akademik. Penelitian ini ingin mengetahui bagaimana peran dosen dalam membentuk perilaku membaca mahasiswa di era digital. Dengan mewawancarai 26 dosen, 38 mahasiswa, 2 pimpinan perpustakaan kampus, dan 1 pejabat dinas pendidikan provinsi, peneliti menemukan bahwa perilaku membaca mahasiswa tidak tumbuh karena kurangnya pembinaan di jenjang pendidikan sebelumnya. Interaksi dengan teknologi informasi dan telekomunikasi di era digital semakin menjauhkan mahasiswa dari perilaku membaca yang diharapkan. Intervensi dari dosen menjadi penting dalam mengondisikan perilaku membaca, yaitu dengan penugasan mencatat dan penugasan membaca. Selain itu, perguruan tinggi perlu mempersiapkan sarana dan prasarana yang mendukung tumbuhnya perilaku membaca mahasiswa.